(untitled) (BIBECHANA, 2023)
The sol-gel spin coating method was used for the preparation of the Zinc Oxide which was coated over polymer, transparent, and glass translucent substrates and characterized with the help of a UV-Vis Spectroscope. The wavelength bandgap of those samples was found to be 296nm, 310.5nm, and 330nm respectively. The actual band gap of ZnO is 388nm. Similarly, their optical bandgap energy calculated by the Tauc Plot method were 3.641eV, 3.385eV, and 3.495 eV respectively. The transparent polymer slide has the lowest wavelength bandgap and the translucent glass slide has the highest. Further, the bandgap’s value differs from its actual value to the difference in the absorption process due to the presence of the substrate. These results suggest that the choice of substrate can significantly impact the optical properties and performance of the zinc oxide thin film. This result can be applied in developing and optimizing zinc oxide thin films for various purposes, such as in solar cells, sensors, and optoelectronics. By carefully selecting the substrate, it may be possible to tailor the bandgap energy and other optical properties of the thin film to better suit the specific application.